Tanggung Jawab Moral Dalam Praktik Penelitian Ilmiah: Ilmu Dan Etika - Maseliya, Maseliya; Silalahi, Suandi (Universitas Sultan Ageng Tirtayasa, 2024)
In the current era of globalization and innovation, society is increasing scientific research through science referring to existing assumptions and conjectures. With the development of increasingly sophisticated technology, society cannot filter out the good and bad impacts of this technology. People are easily influenced by existing information even though its truth has not been tested. Research must maintain integrity and honesty in every stage of research to ensure science does not deviate from the morality of moral and ethical responsibilities. Research must uphold this in every research process. The method used in conducting this research is the literature study research method, which is often called library research, by collecting data and analyzing data from written sources such as books, journals, scientific articles, research reports and other documents. (Juliangkary & Pujiwisata, 2022. The moral and ethical basics that must be implemented by scientists include honesty, obedience and social responsibility. The application of moral basics is very important in protecting public trust in educational science.